A three-dimensional analysis of the center of mass for three different judo throwing techniques - Imamura, R. T.; Hreljac, A.; Escamilla, R. F.; Edwards, W. B. (Journal of Sports Science & Medicine, 2006)
Four black belt throwers (tori) and one black belt faller (uke) were filmed and analyzed in threedimensions using two video cameras (JVC 60 Hz) and motion analysis software. Average linear momentum in the anteroposterior (x), vertical (y), and mediolateral (z) directions and average resultant impulse of uke`s center of mass (COM) were investigated for three different throwing techniques; harai-goshi (hip throw), seoi-nage (hand throw), and osoto-gari (leg throw). Each throw was broken down into three main phases; kuzushi (balance breaking), tsukuri (fit-in), and kake (throw). For the harai-goshi and osoto-gari throws, impulse measurements were the largest within kuzushi and tsukuri phases (where collision between tori and uke predominantly occurs). Both throws indicated an importance for tori to create large momentum prior to contact with uke. The seoi-nage throw demonstrated the lowest impulse and maintained forward momentum on the body of uke throughout the entire throw. The harai-goshi and osoto-gari are considered power throws well-suited for large and strong judo players. The seoi-nage throw is considered more technical and is considered well-suited for shorter players with good agility. A form of resistance by uke was found during the kuzushi phase for all throws. The resistance which can be initiated by tori`s push or pull allows for the tsukuri phase to occur properly by freezing uke for a good fit-in. Strategies for initiating an effective resistance include initiating movement of uke so that their COM is shifted to their left (for right handed throw) by incorporating an instantaneous "snap pull" with the pulling hand during kuzushi to create an opposite movement from uke.